THE MORPHOLOGICAL CHANGE IN SUNFLOWER PLANT UNDER HARDENING CONDITIONS TO DROUGHT TOLERANCE . I. PLANT HEIGHT AND STEM DIAMETER (Baghdad Science Journal, 2009)
The objective of the work was to study the changes in height and stem diameter of sunflower plants during growth stages under hardening conditions to drought tolerance. Field experiments were carried out during the spring season of 2000 and2001. Agricultural practices were made according to recommendations.Asplit-split plots design was used with three replications.The main plots included irrigation treatments:irrigation to100%(full irrigation),75and50%of available water.The sub plots were the cultivars Euroflor and Flame.The sub-sub plots represented four seed soaking treatments:Control(unsoaking), soaking in water ,Paclobutrazol solution(250ppm),and Pix solution(500ppm). The soaking continued for 24 hours then seeds were dried at room temperature until they regained their original weight. Amount of water for each irrigation were calculated to satisfy water depletion in soil using a neutron moisture meter. Results showed that stress 600 and 800Kp caused asignificant decreasing in plan height and stem diameter at most growth stages in both seasons and as a mean of seasons.The decrease in plant height at physiological maturation as a mean of seasons were 12.62 and 14.29%, and stem diameter 11.94 and 9.41%, respectively compared with full irrigation.Euroflor was superior over Flame in plant height at most growth stages during spring season of 2000, while Flame was superior in plant height at most growth stages during spring season of 2001 ,and in stem diameter after 30 days from planting.Soaking the seeds presowing in paclobutrazol and pix solutions decreased plant height at most growth stages in both seasons and as a mean of seasons. The decrease at physiological maturation as amean of seasons were 4.49 and 2.78%compared with unsoaked , and 5.27 and 3.57% compared with soaking in water, respectively.On the other hand,soaking in paclobutrazol and pix solutions increased stem diameter at physiological maturation by 9.78 and 12.18% compared with unsoaked as a mean of seasons. In conclusion, that it could reduce plant height and increase stem diameter to support the plants to drought tolerance by soaking the seeds presowing in water or plant growth regulator